Climate Policy Processes, Local Institutions, and Adaptation Actions : Mechanisms of Translation and Influence - Agrawal, Arun (World Bank, Washington, DC, 2012)
This paper focuses on the experience of the national-level adaptation planning efforts and the lessons that can be derived for more effective adaptation from an examination of local governance of development and natural resources. After examining national level adaptation plans, particularly the NAPAs (National Adaptation Programmes of Action), the paper analyzes the range of institutional instruments and relationships visible in contemporary decentralization reforms. The analysis derives four important lessons for adaptation planning, with special attention to the articulation between local and national level adaptation processes. The paper underlines: a) the diversity of local institutions; b) adaptation strategies, and identifies factors that promote; c) greater accountability; and d) greater equity in national/local relationships.